The standard for program management (Business professional collection, 2017)
"The Standard for Program Management - Fourth Edition differs from prior editions by focusing on the principles of good program management. Program activities have been realigned to program lifecycle phases rather than topics, and the first section was expanded to address the key roles of program manager, program sponsor and program management office. It has also been updated to better align with PMI's Governance of Portfolios, Programs, and Projects: A Practice Guide"--